FPGA Implementation Of A Multihop Wavelength Division Multiplexing (WDM) Ring Router Algorithm - Noordin, Nurul Hazlina (2004)
In order to make the optimum use of a large capacity of optical fibers, a quick routing algorithm is essential. Wavelength Division Multiplexing (WDM) is a technology that is widely employed to fully the huge bandwidth provided by optical fibers and to alleviate electronic bottleneck. WDM network is broadly divided into two categories; single-hop and multi-hop. For multi-hop network, a packet from a source to a destination may have to hop through one or more intermediate nodes. A routing algorithm, Comparing Dimensional Number Routing has been proposed to fully exploit the bandwidth of fiber optics.